Maulānā Dāūdakrta Cāndāyana kā bhāshā svarūpa evaṃ bimbātmaka saṃcetanā - Śāṇḍilya, Śiva Kumāra, 1937- (Bhāshā Prakāśana ; prasāraka Bikrama Pustaka Mandira, 1978)
Linguistic study of the Hindi verse work Cāndāyana by Daud, fl. 1385.